Analisis Yuridis Pelaksanaan Pengaturan Benih Ikan Sidat - Nisa, Roisatun; Wahju, Ronny Irawan; Solihin, Akhmad (Beleid, 2023)
Currently eels are still in the form of enlargement and cannot be cultured. So it is very vulnerable for fishermen to make excessive fishing effort on the glass eelphase. This condition made the government make a policy of limited protection of eel with the Ministerial Decree, Kepmen KP No. 80/KepmenKP/2020. The purpose of this study is to identify the implementation of the Kepmen No. 80/Kepmen-KP/2020, to identify the knowledge of fishers, collectors, and eel rearing units towards the policy, and to identify the perceptions of fishers in the Cimandiri River on the glass eelresources. The method used in this study is normative juridical which focuses on Ministerial Decree Number 80/Kepmen-KP/2020..The results of the study show that the implementation of the Ministerial Decree No. 80/Kepmen-KP/2020 has not been effectively implemented by fishers and collectors. All fishers are not aware of the policy, while 88% of collectors and enlargement all fishers units are aware of it. As many as 60% of fishers stated that there was a change in the decline in glass eeland 67% stated that glass eelresources would not over fishing because fishers did not catch adult (mature) eels. The government needs to increase the internalization and education regarding the importance of preserving eel in nature to stakeholders in Cimandiri River.